National survey of emergency physicians on the risk stratification and acceptable miss rate of acute aortic syndrome. Issue 3 (May 2020) - Ohle, Robert; McIsaac, Sarah; Yan, Justin; Yadav, Krishan; Eagles, Debra; Perry, Jeffrey J.
ABSTRACT: Objectives: One in four cases of acute aortic syndrome are missed. This national survey examined Canadian Emergency physicians' opinion on risk stratification, the need for a clinical decision aid to risk stratify patients, and the required sensitivity of such a tool. Methods: We surveyed 1, 556 members of the Canadian Association of Emergency Physicians. We used a modified Dillman technique with a prenotification email and up to three survey attempts using electronic mail. Physicians were asked 21 questions about demographics, importance of certain high-risk features, investigation options, threshold for investigation, and if a clinical decision tool is required Results: We had a response rate of 32%. Respondents were 66% male, and 49% practicing >10 years, with 59% in an academic teaching hospital. A total of 93% reported a need for a clinical decision aid to risk stratify for acute aortic syndrome. A total of 99.6% of physicians were pragmatic accepting a non-zero miss-rate, two-thirds accepting <1%, and the remaining accepting a higher miss-rate. Conclusions: Our national survey determined that emergency physicians would use a highly sensitive clinical decision aid to determine which patients are at low, medium, or high-risk for acute aortic syndrome. The majority of clinicians have a low threshold (<1%) for investigating for acute aortic syndrome, but accept that a zero miss-rate is not feasible.